Heart transplantation as salvage therapy for progressive prosthetic valve endocarditis due to methicillin-resistant Staphylococcus epidermidis (MRSE). Issue 1 (December 2016) - Borde, J.; Sitaru, G.; Kopp, W.; Ruhparwar, A.; Ehlermann, P.; Lasitschka, F.; Dalpke, A.; Heininger, A.
Abstract Background Prosthetic valve endocarditis (PVE) has the highest in-hospital mortality among all cases of infective endocarditis (IE), it is estimated at about 40 %. Orthotopic heart transplantation (OHT) as a measure of last resort, may be considered in selected cases where repeated surgical procedures and conservative efforts have failed to eradicate persistent or recurrent IE. Only few clinical data are available regarding this rare indication for OHT, since active IE has traditionally been considered as a contraindication for OHT. Case presentation We report on a 55 year old male patient who underwent prosthetic valve replacement with a mechanical valved conduit ten years ago and developed now persistent PVE with severe complications due to methicillin-resistantStaphylococcus epidermidis (MRSE). Repeated surgical procedures and conservative efforts have failed to eradicate the pathogen. Regarding the lack of curative options, salvage OHT was discussed as a measure of last resort. 28 months after the first diagnosis of PVE, the patient was successfully transplanted and is now doing well under close follow-up (6 months post-OHT). Conclusions PVE remains a challenging condition regarding diagnosis and treatment. The presented case underscores the urgent need for an integrated and multidisciplinary approach to patients with suspected and definitive IE - especially in PVE. OHT might be a feasible measure of last resort in selected patients with IE. Our case report adds published clinical experience to this rarely performed procedure and consolidates previous findings.